A Multitarget Therapeutic Peptide Derived From Cytokine Receptors Based on in Silico Analysis Alleviates Cytokine-Stimulated Inflammation - Chang, Chun-Chun; Peng, Shih-Yi; Tsao, Hao-Hsiang; Huang, Hsin-Ting; Lai, Xing-Yan; Hsu, Hao-Jen; Jiang, Shinn-Jong (Frontiers in Pharmacology, 2022)
Septicemia is a severe inflammatory response caused by the invasion of foreign pathogens. Severe sepsis-induced shock and multiple organ failure are the two main causes of patient death. The overexpression of many proinflammatory cytokines, such as TNF-α, IL-1β, and IL-6, is closely related to severe sepsis. Although the treatment of sepsis has been subject to many major breakthroughs of late, the treatment of patients with septic shock is still accompanied by a high mortality rate. In our previous research, we used computer simulations to design the multifunctional peptide KCF18 that can bind to TNF-α, IL-1β, and IL-6 based on the binding regions of receptors and proinflammatory cytokines. In this study, proinflammatory cytokines were used to stimulate human monocytes to trigger an inflammatory response, and the anti-inflammatory ability of the multifunctional KCF18 peptide was further investigated. Cell experiments demonstrated that KCF18 significantly reduced the binding of proinflammatory cytokines to their cognate receptors and inhibited the mRNA and protein expressions of TNF-α, IL-1β, and IL-6. It could also reduce the expression of reactive oxygen species induced by cytokines in human monocytes. KCF18 could effectively decrease the p65 nucleus translocation induced by cytokines, and a mice endotoxemia experiment demonstrated that KCF18 could reduce the expression of IL-6 and the increase of white blood cells in the blood stimulated by lipopolysaccharides. According to our study of tissue sections, KCF18 alleviated liver inflammation. By reducing the release of cytokines in plasma and directly affecting vascular cells, KCF18 is believed to significantly reduce the risk of vascular inflammation.